Introduction. The formation of the Hungarian Information Society in the last ten years - Róbert Sinka (Netcom)
Hungary was an example to follow as one of the initiators of the change that ultimately resulted in the elimination of the Soviet dependence, as well as in the democratization of Eastern-Central European countries. The iron curtain pulled down in 1989 opened up the country to the world. The comfortable protection was suddenly replaced by the new challenges of the global market economy and culture. The forming of the Hungarian information society could have brought one of the most radical changes among these. The present paper studies the successes and failures of the development of the Hungarian information society in the last decade on the basis of the research report (MITJ, 2008) prepared by ITTK (Information Society and Trend Research Centre )